“His Name Does Not Appear”: Missing Voices in Ocean Science and the Invisible Technician at Sea - Hardy, Penelope K. (The Northern Mariner / Le marin du nord, 2025)
This article identifies voices missing from the scientific maritime on two floating laboratories early in the history of oceanography: HMS Challenger in the 1870s and the oceanographic yachts of Prince Albert I of Monaco from the 1880s to 1920s. Using ships’ logs, field journals, personal letters, and newspapers, it elucidates the vital contribution of enlisted sailors, lab technicians, photographers, and illustrators – including women and people of color – to the development of scientific understanding of the oceans. Restoring these actors to their proper place in the record also contributes to an ongoing conversation about the construction of scientific knowledge and authority.